Kontribusi Usahatani Jeruk Siam (Citrus nobilis) Terhadap Pendapatan Rumah Tangga di Poktan Gunung Mekar, Desa Taro, Kecamatan Tegallalang, Kabupaten Gianyar. - WIJAYA, NYOMAN TONY ANGGA; DEWI, RATNA KOMALA; USTRIYANA, NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.2, April 2015, 2016)
Abstract The Contribution of Citrus nobilis Toward Household Incomes at Farmers Group of Gunung Mekar-Village of Taro, District of Tegallalang, Regency of Gianyar. The type of orange which is most widely developed and most widely spread in Indonesia is Citrus nobilis, one of it is in Province of Bali. Gianyar regency is one of the regions potential for developing Siamese orange plants in the Province of Bali, it is because of the suitable environmental condition (soil, climate, altitude and temperature). Gianyar regency is very suitable for Citrus nobilis plants. In the regency of Gianyar, particularly at Taro village, there is a farmer group which called Gunung Mekar farmers group, which has the members of 30 farmers. The main incomes of its members come from Citrus nobilis farming. The result of research regarding the contribution of Citrus nobilis farm toward household incomes at Gunung Mekar farmers group, shows that the source of household incomes of Gunung Mekar farmers group come from the planting of Citrus nobilis, in addition the result of research shows that the contribution toward the household incomes which is originated from Citrus nobilis farming, other farming and non farming. In the final stage of the reseach it is also found out regarding the function of Citrus nobilis marketing activity in Gunung Mekar farmers group at Taro village, District of Tegallalang, Regency of Gianyar. Keywords: Citrus, Contribution, Income, Marketing.